2020
DOI: 10.1017/s1368980020004723
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of recovery in children aged 6–59 months with uncomplicated severe acute malnutrition: a multicentre study

Abstract: Objective: To identify predictors of recovery in children with uncomplicated severe acute malnutrition (SAM). Design: This is a secondary data analysis from an individual randomised controlled trial, where children with uncomplicated SAM were randomised to three feeding regimens, namely RUTF-C, RUTF-L, or A-HPF, under two age strata (6–17 months and 18–59 months) for 16 weeks or until recovery. Three sets of predictors that could influence recovery, viz. child, family, and nutritional pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Exposure to enteric pathogens has been associated with a range of health effects among young children living in low-and middle-income countries, including moderate-to-severe diarrhoea (MSD) (22,25) and chronic undernutrition (13,37). While diarrhoea is understood to contribute to the development and persistence of AM and SAM (12,38,39), and children suffering from AM or SAM are 3 -12 times more likely to die from diarrhoea than non-malnourished children (40), few studies have estimated the burden of enteric pathogens among children suffering or recently recovered from AM or uncomplicated SAM and none have examined the impact of exposure on sustained recovery. A post-hoc analysis of the Global Enterics Multicenter Study demonstrated that not only is enteric pathogen exposure more likely to result in MSD among children suffering from AM compared with children without AM, but also that those exposures are more likely to result in death among children with AM (18).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to enteric pathogens has been associated with a range of health effects among young children living in low-and middle-income countries, including moderate-to-severe diarrhoea (MSD) (22,25) and chronic undernutrition (13,37). While diarrhoea is understood to contribute to the development and persistence of AM and SAM (12,38,39), and children suffering from AM or SAM are 3 -12 times more likely to die from diarrhoea than non-malnourished children (40), few studies have estimated the burden of enteric pathogens among children suffering or recently recovered from AM or uncomplicated SAM and none have examined the impact of exposure on sustained recovery. A post-hoc analysis of the Global Enterics Multicenter Study demonstrated that not only is enteric pathogen exposure more likely to result in MSD among children suffering from AM compared with children without AM, but also that those exposures are more likely to result in death among children with AM (18).…”
Section: Discussionmentioning
confidence: 99%
“…However, the nutritional recovery appears slower among children discharged from the hospital compared with children treated in the community, although the reasons for this slower rate of recovery are not clearly understood [5,6]. Multiple factors, including differences in the etiology of wasting among individual children, the presence of comorbidities, and socioeconomic vulnerabilities, all influence nutritional recovery following hospital discharge [7,8].…”
Section: Introductionmentioning
confidence: 99%